SWATH-MS based quantitative proteomics analysis to evaluate the antileishmanial effect of Commiphora wightii- Guggul and Amphotericin B on a clinical isolate of Leishmania donovani - Bar Routaray, Chinmayee; Bhor, Renuka; Bai, Shakuntala; Kadam, Nitin Suryakant; Jagtap, Surabhi; Doshi, Pooja Jignesh; Sundar, Shyam; Sawant, Sangeeta; Kulkarni, Mahesh J.; Pai, Kalpana (Journal of Proteomics, 2020)
The present study provides comprehensive proteomics analyses of the response of L. donovani parasite to pharamacological stress in vitro. Identification of differentially expressed proteins with associated molecular functions and metabolic pathways, clearly provides an insight into the potential mechanism of the antileishmanial effects as well as a comparative response of the parasite to Guggul and AmB. Treatment of parasite with AmB results in an enhanced modulatory mechanism to counteract the drug induced stress which may have contributed to relapse. In the case of Guggul treatment, an effective antipromastigote activity was observed, which is being reported for the first time. Thus, a deeper understanding of the molecular pathways in the Leishmania parasite in response to pharmacological stress would help in designing novel and effective strategies in targeting the key molecules essential for parasite survival. It will also help in screening of new lead molecules targeting these vital pathways which could be used as an adjunct therapy along with the limited repertoire of antileishmanial drugs.